120k views
4 votes
Even even more questions


(5+2i) - (7 + i)

(8-i)+(3-i)

(-5i)(6+5i)

(-7i)(7i)

(4+4i)(3-6i)

(2i)(3+5i)(-5+8i)

(-4-7i)^2

(5+7i)(5-7i)

4/-8i

8+2i/7i

User Scurioni
by
7.2k points

2 Answers

4 votes

For many of these, it is important to remember:


i=√(-1) ---->
i^(2) = -1

Answer:


(5 + 2i) - (7+i) = 5 + 2i - 7 - i = -2 + i


(8-i)+(3-i) = 8-i+3-i=11-2i

For the multiplication ones, we have to foil:


(-5i)(6+5i) = -30i - 25i^(2) = -30i + 25


(-7i)(7i) = -49i^(2) = -49(-1) = 49


(4+4i)(3-6i)=12-24i+12i-24i^(2) = 12-12i-24(-1) = 36-12i


(2i)(3+5i)(-5+8i) = (6i+10i^(2) )(-5+8i) = (6i+10(-1))(-5+8i)\\=(6i-10)(-5+8i)=-30i+48i^(2) +50-80i=48(-1)+50-110i=2-110i


(-4-7i)^(2) = (-4-7i)(-4-7i)=16+28i+28i+49i^(2) = 16+56i-49 = 56i-33


(5+7i)(5-7i) = 25-35i+35i-49i^(2) = 25 -49(-1)=25+49 = 74


(4)/(-8i) =-(1)/(2i)=-(1)/(2i)((i)/(i))=-(i)/(2i^(2) ) =-(i)/(2(-1)) =(i)/(2)


(8+2i)/(7i)=(8+2i)/(7i)((i)/(i) )=(8i+2i^(2) )/(7i^(2) ) =(8i+2(-1))/(7(-1)) =(8i-2)/(-7) =(2)/(7) -(8i)/(7)

User SHINIGAMI
by
7.1k points
3 votes

Answer:

See below

Explanation:

Let's go through each expression one by one:

1.
\tt (5 + 2i) - (7 + i)


\tt = 5 + 2i - 7 - i


\tt = (5 - 7) + (2i - i)


\tt = -2 + i

2.
\tt (8 - i) + (3 - i)


\tt = 8 - i + 3 - i


\tt = (8 + 3) + (-i - i)


\tt = 11 - 2i

3.
\tt (-5i)(6 + 5i)


\tt = -5i \cdot 6 - 5i \cdot 5i


\tt = -30i - 25i^2

Since
\tt i^2 = -1, replace
\tt i^2 with
\tt -1:


\tt = -30i - 25(-1)


\tt = -30i + 25

4.
\tt (-7i)(7i)


\tt = -7i \cdot 7i


\tt = -49i^2

Since
\tt i^2 = -1, replace
\tt i^2 with
\tt -1:


\tt = -49(-1)


\tt = 49

5.
\tt (4 + 4i)(3 - 6i)


\tt = 4(3) + 4(3)(-6i) + 4i(3) + 4i(-6i)


\tt = 12 - 24i + 12i - 24i^2

Since
\tt i^2 = -1, replace
\tt i^2 with
\tt -1:


\tt = 12 - 12i - 24(-1)


\tt = 36 - 12i

6.
\tt (2i)(3 + 5i)(-5 + 8i)

First, multiply the first two terms:


\tt = (2i)(3 + 5i) \cdot (-5 + 8i)


\tt = (6i + 10i^2)(-5 + 8i)


\tt = (10i^2 - 6i)(-5 + 8i)

Replace
\tt i^2 with
\tt -1:


\tt = (-10 - 6i)(-5 + 8i)

Now, distribute:


\tt = 50 + 30i - 40i + 24i^2

Replace
\tt i^2 with
\tt -1:


\tt = 50 - 10i

7.
\tt (-4 - 7i)^2


\tt = (-4 - 7i)(-4 - 7i)

Use FOIL:


\tt = 16 + 28i + 28i + 49i^2

Replace
\tt i^2 with
\tt -1:


\tt = 16 + 56i - 49


\tt = -33 + 56i

8.
\tt (5 + 7i)(5 - 7i)

Use the difference of squares formula:
\tt a^2 - b^2 = (a + b)(a - b)


\tt = (5 + 7i)(5 - 7i)


\tt = 5^2 - (7i)^2


\tt = 25 - 49i^2

Replace
\tt i^2 with
\tt -1:


\tt = 25 + 49


\tt = 74

9.
\tt (4)/(-8i)

Multiply the numerator and denominator by
\tt i to eliminate the denominator:


\tt = (4i)/(-8i^2)

Replace
\tt i^2 with
\tt -1:


\tt = (4i)/(8)


\tt = (1)/(2)i

10.
\tt (8 + 2i)/(7i)

Multiply the numerator and denominator by
\tt -i to eliminate the denominator:


\tt = ((8 + 2i)(-i))/(7i(-i))


\tt = (-8i - 2i^2)/(-7)

Replace
\tt i^2 with
\tt -1:


\tt = (-8i + 2)/(-7)


\tt = (2 - 8i)/(7)

User NoahR
by
7.2k points